ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN CROSSWORD PUZZLE PADA MUATAN PEMBELAJARAN PENDIDIKAN PANCASILA - Ismawati I. Sugau; Nasriani; Hamna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Pancasila Education learning in class IV of SD Negeri 2 Bokat tended to be passive and less engaging due to the dominance of the lecture method , resulting in low student participation and understanding of the material. This study aims to describe the use of crossword puzzle learning media as an alternative to improve learning effectiveness. The method used is descriptive qualitative with research subjects consisting of one teacher and three fourth-grade students. Data collection techniques included observation, interviews, and documentation, which were then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of crossword puzzle media significantly improved student understanding and learning outcomes. This medium successfully created a more interactive, collaborative, and enjoyable learning atmosphere. Students became more motivated, active, and able to enhance their critical thinking skills and memory of Pancasila values. Effective implementation was supported by five indicators: material explanation, IT-assisted puzzle creation, clue formulation, individual and group task distribution, and the provision of rewards